The PENGARUH PIJAT OKETANI TERHADAP KELANCARAN PRODUKSI ASI PADA IBU NIFAS DI RSKIA ANNISA BANJARMASIN - Sempurna Ningdia, Ratna; Dwi Rahmawati; Nurul Hidayah (LPPM Universitas Sari Mulia, 2023)
Background:Smooth breast milk (ASI) production is very important for ensuring a food source for breastfeeding infants. The smooth flow of breast milk is influenced by many factors, or multifactorial causes. Approximately 30% of postpartum mothers are unable to breastfeed their babies. About 35% of breastfeeding mothers face difficulties in providing breast milk due to problems with milk production. According to the 2021 Health Profile Report from the South Kalimantan Provincial Health Office, the rate of exclusive breastfeeding in South Kalimantan in 2020 was 50.16%, while in Banjarmasin City it was only 32.14% for babies aged 0–6 months. Mothers who are unable to breastfeed in the early days of the postpartum period are often affected by anxiety and fear over low milk production, as well as a lack of knowledge about the breastfeeding process. Therefore, efforts to facilitate breast milk production in postpartum mothers are necessary. Objective:To evaluate and assess the effect of Oketani massage on the smooth production of breast milk in postpartum mothers at RSKIA Annisa Banjarmasin. Method:This study is a quantitative research using a quasi-experimental design with a one-group pretest-posttest approach. Sampling was done using purposive sampling technique, with a total of 30 postpartum mothers who gave birth at RSKIA Annisa Banjarmasin. Data were analyzed using the Paired T-Test. Results:The results showed that the mean breast milk production before Oketani massage was 8.93, increasing to 38.30 after the massage was administered. The significance value was p = 0.000 (≤ 0.05). Conclusion:There is a significant effect of Oketani massage on the smooth production of breast milk in postpartum mothers at RSKIA Annisa Banjarmasin. Keywords: Breast Milk Production, Oketani Massage